The 21st century skills of the ALS graduates enrolled in the College of Engineering and Information Technology a basis for college policy recommendation - Lapid-Ladwingon, Ruth; Valdez, Angeline B.; Mariani, Mathew Jun P. (2019)
The advancements in the world come with the demand to acquire 21st century skills that would able learners to cope with global trends. These skills are emphasized by instructions and strategies employed in formal teaching-learning environments. However, the number of school dropouts and out-of-school youth increased pressing the Department of Education to implements alternative delivery modes and satisfy its mandate of Education for All (EFA). One of these is the Alternative Learning System (ALS), which allows learners to attain education through non-formal and informal approaches. This paper identified the level of 21st century skills of the ALS graduates who are enrolled in the different programs of the College of Engineering and Information Technology of Kalinga State University for the school year 2018-2019. It employed the qualitative research design to describe of the 21st-year 2018-2019. It employed the qualitative research design to describe the level of 21st century skills possessed by the ALS graduates and the teaching experiences of the instructors who handle classes with ALS graduates and the teaching experiences of the instructors who handle classes with ALS graduates. It used a modified survey questionnaire based on the Survey for Measuring 21st Century Teaching and Learning (Hixzon et al., 2012) and an unstructured interview. It was revealed through frequency count and computation of weighted mean that the 21st century skills of the ALS graduates are in the below-average level with a numerical value of 2.33. The college may require these ALS graduates to take bridging subjects as an admission policy and pass a semestral screening examination to be retained in the course they are enrolled in.
Keywords: Alternative Learning System (ALS)